II. Documenta '59 : Malerei. - Bode, Arnold; von Buttlar, Herbert; Grohmann, Will; Haftmann, Werner; Hunter, Sam; Lauritzen, Lauritz; Lemke, Heinz; Schmalenbach, Werner (Köln : Verlag M. DuMont Schauberg, 1959)
Acht, René ; Adam, Henri-Georges ; Afro ; Appel, Karel ; Ardon, Mordechai ; Arp, Hans (Jean) ; Bacon, Francis ; Bargheer, Eduard ; Battke, Heinz ; Batz, Eugen ; Baumeister, Willi ; Bazaine, Jean ; Baziotes, William ; Beaudin, André ; Beck, Gustav Kurt ; Beckmann, Max ; Bergman, Anna-Eva ; Berke, Hubert ; Bertrand, Gaston ; Bissier, Julius ; Bissière, Roger ; Bluhm, Norman ; Boccioni, Umberto ; Bodmer, Walter ; Bonnet, Anne ; Braque, Georges ; Brauner, Victor ; Brooks, James ; Buchheister, Carl ; Burri, Alberto ; Burssens, Jan ; Camaro, Alexander ; Capogrossi, Giuseppe ; Cassinari, Bruno ; de Castro, Sergio ; Cavallon, Giorgio ; Chagall, Marc ; De Chirico, Giorgio ; Corneille ; Corpora, Antonio ; Cuixart, Modest ; d'Orgeix, Christian ; Dahmen, Karl Fred ; Davie, Alan ; Degottex, Jean ; Delaunay, Robert ; Delvaux, Paul ; Deyrolle, Jean ; Dorazio, Piero ; Dova, Gianni ; Dubuffet, Jean ; Dufour, Bernard ; Eble, Theo ; Ernst, Max ; Estève, Maurice ; Fassbender, Joseph ; Fautrier, Jean ; Fedier, Franz ; Feito, Luis ; Fontana, Lucio ; Francis, Sam ; Frankenthaler, Helen ; Gaul, Winfred ; Geiger, Rupprecht ; Georges, Claude ; Giacometti, Alberto ; Gilles, Werner ; Gillet, Roger Edgar ; Goldberg, Michael ; Goller, Bruno ; Gorky, Arshile ; Gottlieb, Adolph ; Götz, K.O. (Karl Otto) ; Greis, Otto ; Guston, Philip ; Hantaï, Simon ; Hartigan, Grace ; Hartung, Hans ; Hausner, Rudolf ; Heldt, Werner ; Herbin, Auguste ; Herkenrath, Peter ; Hilton, Roger ; Hoehme, Gerhard ; Hofmann, Hans ; Inoue, Yuichi ; irolli, Renato ; Iseli, Rolf ; Jorn, Asger ; Kandinsky, Wassily ; Kantor, Tadeusz ; Kemeny, Zoltan ; de Kermadec, eugène ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kline, Franz ; Kokoschka, Oskar ; de Kooning, Willem ; Lam, Wifredo ; Landuyt, Octave ; Lanskoy, André ; etc.
II. Documenta '59, Kunst nach 1945, Internationale Ausstellung, 11. Juli - 11. Oktober 1959, Museum Fridericianum, Kassel
Duits
boek